Biopharmacotechnical and physical properties of solid pharmaceutical forms containing rutin commercially acquired in Juiz de Fora city, Brazil - Thiago Maurício de Souza Pinto; Fabrini Luiz Alves Almeida; Julianna Oliveira de Lucas Xavier; Glauciemar Del-; Ana Lúcia Santos de Matos Araújo; José de Jesus Ribeiro Gomes de Pinho; Maria Silvana Alves; Orlando Vieira de Sousa (Universidade Estadual de Maringá, 2020)
Rutin is a flavonoid used in clinical practice to treat capillary fragility and prevent bleeding due to its wide variety of pharmacological actions, including antioxidant, anti-inflammatory, anti-allergic, antiproliferative, and anticarcinogenic activities. In this study, the biopharmacotechnical and physical properties of film-coated tablets containing rutin marketed in drugstores were evaluated. Using samples from three batches called A, B and C, we determined the average weight, disintegration time, hardness, content and dissolution profile, and kinetics of the tablets. The samples demonstrated average weight of 457.45 ± 12.32 to 449.15 ± 8.95 mg; disintegration time, 30.17 ± 2.14 to 15.17 ± 2.14 min; hardness, 1.92 ± 0.55 to 1.69 ± 0.36 Kgf; and rutin content, 18.34 ± 1.21 to 15.66 ± 1.29 mg. After 90 min, the dissolution profile showed 52.65, 41.80, and 79.2% for A, B, and C, respectively. The results imply that the non-conformities of the tested products can significantly compromise the drug's therapeutic efficacy.